Criminal Liability of a Notary for Violation of The Principle of Precaution : Study Decision Number 88/PID.B/2022/PN MLG - Sari, Riski Diana; Djatmika, Prija; Kawuryan, Endang Sri (International Journal of Business, Law, and Education, 2024)
Notary Public own authority in matter making deed authentic so notaries also have responsibility on deed in making something deed authentic. Notary Public required always Act in a way Be careful in making deed, must research all true and relevant facts based on applicable laws. However sometimes in room scope There is also a notary rules-based habits that don't contained in the Law Position Applicable notary, p is executed based on law habit like one authority Notary Public that is in make cover note. So far This Notary Public make cover note only based on law habit Because no exists umbrella law to making cover note Notary Public. So that need exists repair rule law related with making cover note notary so that in the future Far Better. Study This use study law normative with use approach used is Approach Law (statute approach), Approach Conceptual (conceptual approach) and Approach Case (case approach). Result of study This i.e. Notary Public stated join in as well as do follow criminal Because has fulfil it elements in Article 378 of the Criminal Code in conjunction with Article 55 paragraph (1) of the Criminal Code and also fulfil elements responsibility criminal that is exists ability responsible for the maker , relationship inner between si maker and his actions in the form intentional ( dolus ) or negligence (culpa) and not exists reason deletion error or No There is reason forgiving so that Notary Public in case This can be requested accountability criminal on what has been done . Repair law related with cover note can formulated Far Better with fulfil condition justice and power To use as well as connected with 3 (three) objectives law in a way theoretical